Social change and human development concept and results - Silbereisen, R. K. (Rainer K.) 1944-; Chen, Xinyin; SAGE Knowledge (Online service). (Los Angeles, Calif. Sage, 2010)
"Today's world is characterized by a set of overarching trends that often come under the rubric of social change. In this innovative volume, Rainer K. Silbereisen and Xinyin Chen bring together, for the first time, international experts in the field to examine how changes in our social world impact our individual development.Divided into four parts, Human Development and Social Change explores the major socio-political and technological changes that have taken place around the world - from the rapid upheavals in 1990s Europe to the gradual changes in parts of East Asia - and explains how these developments interplay with human development across the lifespan."-Provided by publisher.
How social change affects individual adaptation -- Part I. Dynamic of social change and individual responses ; A challenge-response-model in research on social change ; Life management in developmental settings of modernity: challenges to the adaptive self ; Conceptualizing the dynamics of lives and historical times: life course phenomena, institutional dynamics and sociohistorical change -- Part II. Determinants on the individual level ; Globalization, institutional filters and changing life course. patterns in modern societies: a summary of the results from the Globalife-Project ; Demands of social change and psychosocial adjustment: results from the Jena study ; Globalization, social inequality, and individual agency in human development: social change for better or worse? -- Part III. Transitions and transformations in international perspective ; Institutional responses to social change in comparative perspective: Germany and Poland ; Class, stratification, and personality under conditions of apparent social stability and of radical social change: a multi-nation comparison ; Children's socioemotional functioning and adjustment in the changing Chinese society ; Social change and premarital sexual behavior and attitudes in Vietnam ; Social change and transition experiences among young adults in Britain ; Political elites as an agent of social change: the Polish perspective.
Includes bibliographical references and index.
Keywords: Social change; Developmental psychology; Electronic books